There is no anaerobic work capacity replenishment at critical power intensity: An indirect evidence - Nakamura, F. Y.; Pereira, G. [UNESP]; Hill, D. W.; Berthoin, S.; Kokubun, Eduardo [UNESP] (Elsevier France-editions Scientifiques Medicales Elsevier, 2008)
Aim. - This study aimed to test if investigate whether the anaerobic work capacity is replenished while exercising at critical power intensity. Then, a known exercise duration, which demands high anaerobic energy contribution, was compared to intermittent exercise duration with passive and active (cycling at critical power intensity) rest periods.Methods. - Nine participants performed five sessions of testing. From the 1st to the 3rd sessions, individuals cycled continuously at different workloads (P-high, P-intermediate and P-low) in order to estimate the critical power and the anaerobic work capacity. The 4th and 5th sessions were performed in order to determine the influence of anaerobic work capacity replenishment oil exercise duration. They consisted of manipulating the resting type (passive or active) between two cycling efforts. The total exercise duration was determined by the sum of the two cycling efforts duration.Results. - The exercise duration under passive resting condition (408.0 +/- 42.0 s) was longer (p<0.05) than known exercise duration at P-intermediate (T-intermediate = 305.8 +/- 30.5 s) and than exercise duration performed under active resting conditions (T-active = 304.4 +/- 30.7s). However, there was no significant difference between T-intermediate and T-active.Conclusion. - These results demonstrated indirect evidence that the anaerobic work capacity is not replenished while exercising at critical power intensity. (C) 2008 Elsevier Masson SAS. All rights reserved.
Keywords: Cycling; Critical power; Exhaustion time